Oeuvres politiques : tome 8 : l'armée anglaise : la chute de Kars : la révolution espagnole. - Marx, Karl; Molitor, J.; Riazanoff, N. (Paris : Costes, 1931)
Bibliotheek E. Anseele
Frans
Meerdelige publicatie